PENGARUH KEPUASAN KERJA, KOMITMEN ORGANISASI TERHADAP KUALITAS JASA KARYAWAN CALL CENTER - Dita Old Berliyanti; Maylani Imelda (Media Riset Bisnis & Manajemen, 2008)
Service delivery process is happened with interaction between employees and customers. Employees who had commitred to the company and satisfied with their's job would give service better to the customer. The purpose of this study is to examine whether job satisfaction, organizational commitment influence service quality. Data collected by distributing questionnaire to 100 respondents at call center Bank X. Using Structural Equation Modelling (SEM), result of the experiment indicate that there are positively influence between job satisfaction, organizational commitment on service quality.Keywords : Job Satisfaction, Organizational Commitment, Service Quality